Genetic optimization of Brillouin scattering gain in subwavelength-structured silicon membrane waveguides. (June 2023) - Nuño Ruano, Paula; Zhang, Jianhao; Melati, Daniele; González-Andrade, David; Le Roux, Xavier; Cassan, Eric; Marris-Morini, Delphine; Vivien, Laurent; Lanzillotti-Kimura, Norberto Daniel; Alonso-Ramos, Carlos
Abstract: On-chip Brillouin optomechanics has great potential for applications in communications, sensing, and quantum technologies. Tight confinement of near-infrared photons and gigahertz phonons in integrated waveguides remains a key challenge to achieving strong on-chip Brillouin gain. Here, we propose a new strategy to harness Brillouin gain in silicon waveguides, based on the combination of genetic algorithm optimization and periodic subwavelength structuration to engineer photonic and phononic modes simultaneously. The proposed geometry is composed of a waveguide core and a lattice of anchoring arms with a subwavelength period requiring a single etch step. The waveguide geometry is optimized to maximize the Brillouin gain using a multi-physics genetic algorithm. Our simulation results predict a remarkable Brillouin gain exceeding 3300 W −1 m −1, for a mechanical frequency near 15 GHz. Highlights: A single-etch step silicon membrane providing high Brillouin gain is proposed. The structure design is optimized using a genetic algorithm. The structure exhibits a robust tolerance to fabrication defects.